Preparation method of ultra-thin carbon nitride / polyacrylonitrile / ferric oxide composite material and application of composite material in hydrogen production by photoreforming PET (Polyethylene Terephthalate)

By preparing ultra-thin carbon nitride/polyacrylonitrile/ferrooxide composites, the problems of low efficiency and poor stability of existing photocatalysts in the hydrogen production process of PET are solved, and efficient photocatalytic hydrogen production effect is achieved.

CN120325320APending Publication Date: 2025-07-18JIANGSU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510477656.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-16
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

In the process of photoreforming PET hydrogen production, existing photocatalysts have problems such as the limitation of visible light absorption boundary, fast recombination rate of photogenerated electron-hole pairs, and small specific surface area, which leads to low hydrogen production efficiency and poor stability, making it difficult to achieve an efficient and stable electron coordination mechanism.

Method used

By copolymerizing melamine with polyacrylonitrile, the carbon site is introduced to replace the inactive nitrogen site in carbon nitride, and a chemical electron migration channel is formed with the metal oxide α-Fe2O3 to prepare ultra-thin carbon nitride/polyacrylonitrile/ferrous oxide composite material, and optimize the carrier transmission path and photoresponse range.

Benefits of technology

The hydrogen production performance of photoreconstructed PET is significantly improved. The hydrogen production volume reaches 557.081μmol g-1h-1 under visible light, which is 3.93 times that of bulk carbon nitride, and the output is 4143μmol g-1h-1 under AM 1.5G light source, which is 6.2 times that of bulk carbon nitride, with high efficiency and low cost advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120325320A_ABST
    Figure CN120325320A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photocatalytic composite material synthesis, and discloses a preparation method of an ultrathin carbon nitride / polyacrylonitrile / ferric oxide composite material and application of the ultrathin carbon nitride / polyacrylonitrile / ferric oxide composite material in hydrogen production by photoreforming PET. Firstly, polyacrylonitrile and melamine are subjected to high-temperature calcination to prepare a precursor compound; then, FeCl3. 6H2O, absolute ethyl alcohol, H2O and CH3COONa are subjected to a hydrothermal reaction, and red turbid liquid is prepared; and finally, calcining the red suspension and the precursor compound twice to prepare the ultra-thin carbon nitride / polyacrylonitrile / ferric oxide composite material. According to the material, firstly, melamine and polyacrylonitrile are copolymerized, carbon sites are introduced to replace part of inactive nitrogen sites in carbon nitride, then metal oxide alpha-Fe2O3 is introduced to form a chemical electron migration channel, the migration rate of photon-generated carriers is increased, meanwhile, the light response range is widened, and then the hydrogen production performance of photo-reforming PET is improved. The method has the technical advantages of high efficiency, no pollution and low cost, and is expected to be popularized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of the synthesis of photocatalytic composite materials, relates to the preparation of photocatalysts, and particularly relates to a synthesis method of an ultrathin carbon nitride / polyacrylonitrile / iron oxide composite material and its application to the efficient hydrogen production by photoreforming PET. Background Art

[0002] As one of the most potential clean energy sources, hydrogen energy has core advantages such as high energy density, pollution-free combustion products (only water is generated), and can be stored and transported, and is regarded as a key carrier to achieve the carbon neutrality goal. However, traditional hydrogen production technologies (such as natural gas reforming or electrolysis of water) still rely on fossil energy or high-energy-consuming processes, and there is an urgent need to develop green and low-cost sustainable hydrogen production paths. Photocatalytic technology uses solar energy to drive chemical reactions, providing an ideal way for hydrogen production. Among them, the technology of photocatalytic reforming of polyethylene terephthalate (PET) plastic waste to produce hydrogen has attracted much attention, which has the dual benefits of "plastic resource utilization" and "clean energy production": on the one hand, it can convert the difficult-to-degrade PET into high-value-added hydrogen, alleviating the problem of white pollution; on the other hand, it directly uses solar energy through photocatalytic reactions, avoiding the high energy consumption defects of traditional thermal catalytic reforming. A large number of inorganic materials (such as TiO2, ZnIn2S4, CdS, etc.) have been developed as important catalysts for photocatalytic reforming of PET to produce hydrogen. However, due to bottlenecks such as the environmental toxicity of heavy metals, high cost, narrow light response range, fast carrier recombination rate, and insufficient surface active sites, the hydrogen production efficiency is low and the stability is poor, seriously restricting its practical application.

[0003] Graphitic carbon nitride (g-C3N4) has become a research hotspot in the field of photocatalysis due to its low cost, high chemical stability, and suitable energy band structure. However, traditional g-C3N4 still has significant defects: (1) the visible light absorption boundary is limited to about 460 nm, and the utilization rate of long-wavelength photons is low; (2) the recombination rate of photo-generated electron-hole pairs is fast, and the quantum efficiency is limited; (3) two-dimensional sheets are easy to stack, resulting in a small specific surface area and insufficient exposure of active sites. Research shows that by constructing a strong electron coupling interface (such as heterojunction, chemical bond bridging, or atomically dispersed active sites), the energy band structure of the material can be effectively regulated, the directional separation of charges can be promoted, and the light response range can be broadened. For example, coupling with a narrow-bandgap semiconductor (such as Fe2O3) can form a stepped energy level arrangement to enhance the visible light capture ability; while introducing a conductive polymer (such as polyacrylonitrile, PAN) as an interfacial medium can optimize the carrier transport path through π-π conjugation or chemical bonding, inhibiting the recombination loss. However, existing composite materials mostly rely on physical mixing or weak interfacial interactions, and it is difficult to achieve an efficient and stable electron synergistic mechanism. Therefore, designing a carbon nitride-based composite system with strong electron coupling bonds is an important direction to break through the bottleneck of its photocatalytic performance. Summary of the Invention

[0004] In order to solve the problems existing in the prior art, the present invention aims to provide a method for preparing an ultra-thin carbon nitride / polyacrylonitrile / iron oxide composite material. First, melamine and polyacrylonitrile are copolymerized to introduce carbon sites to replace some inactive nitrogen sites in carbon nitride, and then metal oxide (α-Fe2O3) is introduced to form a chemical electron migration channel, which increases the migration rate of photogenerated carriers and enhances the light response range, thereby improving the hydrogen production performance of photo-reforming PET.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing an ultra-thin carbon nitride / polyacrylonitrile / iron oxide composite material comprises the following steps:

[0007] (1) mixing polyacrylonitrile and melamine uniformly and grinding them, then transferring the mixture into a crucible and heating the mixture in a muffle furnace at 540-560° C. for 4-6 hours, cooling the mixture to room temperature, washing the mixture with distilled water and anhydrous ethanol, centrifuging the mixture, collecting the precipitate, and drying the mixture to obtain a precursor composite;

[0008] (2) FeCl3·6H2O, anhydrous ethanol and H2O are fully stirred, and then CH3COONa is added, and the mixture is transferred to a reactor, and hydrothermally treated at 170-190°C for 10-14 hours, and naturally cooled to room temperature, washed with deionized water, and the red precipitate is collected by centrifugation, dried and dehydrated, and the obtained red powder α-Fe2O3 is prepared into a red suspension of a certain concentration;

[0009] (3) The red suspension obtained in step (2) is dripped into the precursor composite prepared in step (1), and then distilled water is added to mix it thoroughly, and then it is transferred to a crucible and calcined for the first time at 540-560° C. in a muffle furnace for 4-6 hours. After cooling to room temperature, it is calcined for the second time at 540-560° C. in a muffle furnace for 1-2 hours to obtain an ultra-thin carbon nitride / polyacrylonitrile / iron oxide composite material.

[0010] In step (1), the mass ratio of polyacrylonitrile to melamine is 0.02g:2g.

[0011] Furthermore, in step (1), the temperature of the heating reaction is 550° C. and the time is 4 hours.

[0012] In step (2), the usage ratio of FeCl3·6H2O, anhydrous ethanol, water and CH3COONa is 0.273 g:10 mL:0.7 mL:0.8 g.

[0013] Furthermore, in step (2), the temperature of the hydrothermal treatment is 180° C. and the time is 12 h.

[0014] In steps (1) and (2), the drying temperature is 60 °C.

[0015] In step (3), the dosage ratio of the red suspension to the precursor complex is 1 - 4 mL: 2 g; among them, the concentration of the red suspension is 0.1 mg / mL.

[0016] Furthermore, in step (3), the temperature of the first calcination is 550 °C and the time is 4 h; the temperature of the second calcination is 550 °C and the time is 1.5 h.

[0017] The in-depth analysis of the ultrathin carbon nitride / polyacrylonitrile / iron oxide composite material prepared by the present invention is determined by X-ray diffraction (XRD), Fourier transform infrared (FTIR), and X-ray photoelectron spectroscopy (XPS), and the surface morphology is measured by scanning electron microscopy (SEM) and transmission electron microscopy (TEM).

[0018] Another object of the present invention is to apply the prepared ultrathin carbon nitride / polyacrylonitrile / iron oxide composite material to photocatalytic reforming of PET to produce hydrogen.

[0019] Experimental process of photocatalytic reforming of PET:

[0020] Disperse 20 mg of the sample in 50 mL of 1 M PET hydrolysis solution, and use 250 μL of aqueous H2PtCl6·6H2O solution for in-situ photoreduction to load platinum on the catalyst. Then evacuate for 30 min to remove the residual gas contained in the system. Irradiate under a 300 W xenon lamp equipped with a filter (λ>420 nm and AM 1.5G), and continuously stir the solution. Analyze the hydrogen production by gas chromatography, use high-purity nitrogen as the carrier gas throughout the reaction process, record the data every 1 h, take 5 h as a cycle, and finally convert the peak area shown in the chromatogram in gas chromatography into the actual hydrogen production amount, with the unit of μmol g -1 h -1 。

[0021] Photoelectrochemical test of the ultrathin carbon nitride / polyacrylonitrile / iron oxide composite material; test of Mott, transient photocurrent density and electrochemical impedance under a CHI 760E electrochemical workstation. The test is carried out at room temperature, using an Ag / AgCl electrode as the reference electrode, a platinum wire as the counter electrode, and an FTO conductive glass sheet spin-coated with the ultrathin carbon nitride / polyacrylonitrile / iron oxide composite material as the working electrode. The electrolyte in the electrolytic cell is 0.5 M Na2SO4.

[0022] The beneficial effects of the present invention are:

[0023] In the present invention, melamine and polyacrylonitrile are calcined to generate a precursor, and α-Fe2O3 is synthesized by a hydrothermal method. Subsequently, the two precursors are calcined to synthesize an ultrathin carbon nitride / polyacrylonitrile / iron oxide composite material, thereby achieving the effect of improving the photocatalytic reforming hydrogen production performance of carbon nitride. The present invention photoreforms PET under visible light, and the hydrogen production reaches 557.081 μmol g -1 h -1 , which is 3.93 times the hydrogen production efficiency of bulk carbon nitride. Under the irradiation of an AM 1.5G light source, photoreforming PET, the hydrogen production reaches 4143 μmol g -1 h -1 , which is 6.2 times the hydrogen production efficiency of bulk carbon nitride. It has the technical advantages of high efficiency, pollution-free, and low cost, and is expected to be popularized. Description of the Drawings

[0024] Figure 1 SEM and TEM images of each product; (a) SEM image of bulk carbon nitride; (b) SEM image of ultrathin carbon nitride / polyacrylonitrile / iron oxide composite material; (c) and (d) TEM images of ultrathin carbon nitride / polyacrylonitrile / iron oxide composite material.

[0025] Figure 2 are: (a) FTIR spectra of ultrathin carbon nitride / polyacrylonitrile / iron oxide composite materials and bulk carbon nitride prepared by different examples; (b) XRD patterns of ultrathin carbon nitride / polyacrylonitrile / iron oxide composite materials, bulk carbon nitride, and α-Fe2O3 prepared by different examples; (c) XPS spectrum of ultrathin carbon nitride / polyacrylonitrile / iron oxide composite material; (d-i) UV-vis DRS spectra and corresponding Tauc plots of sulfur-doped ultrathin carbon nitride and bulk carbon nitride prepared by different examples.

[0026] Figure 3 XPS spectra of ultrathin carbon nitride / polyacrylonitrile / iron oxide composite material and bulk carbon nitride.

[0027] Figure 4 are the Mott plots of bulk carbon nitride (a) and the Mott plots of ultrathin carbon nitride / polyacrylonitrile / iron oxide composite materials prepared by different examples (b-e).

[0028] Figure 5 are the photocurrent plots (a), impedance plots (b), transient fluorescence plots (c), steady-state fluorescence plots (d), ESR plots (e-f), EPR plots (g), and band structure plots (h) of ultrathin carbon nitride / polyacrylonitrile / iron oxide composite materials and bulk carbon nitride prepared by different examples.

[0029] Figure 6Hydrogen production performance graphs of ultrathin carbon nitride / polyacrylonitrile / iron oxide composites and bulk carbon nitride prepared for different examples under visible light (a-b) and hydrogen production performance graphs under AM 1.5G (c-d). Detailed Description of the Invention

[0030] The present invention will be described in detail below with reference to embodiments, so that those skilled in the art can better understand the present invention. However, the present invention is not limited to the following embodiments.

[0031] Example 1

[0032] A. Synthesis of Ultrathin Carbon Nitride / Polyacrylonitrile / Iron Oxide 1 (UCN / PAN / α-Fe2O3-1) Composite

[0033] (1) 20 mg of polyacrylonitrile and 2 g of melamine were mixed evenly and then ground. Subsequently, the mixture was transferred to a crucible and heated in a muffle furnace at 550 °C for 4 h. After cooling to room temperature, it was washed and centrifuged with distilled water and absolute ethanol, the precipitate was collected, and dried overnight at 60 °C.

[0034] (2) 0.273 g of FeCl3·6H2O was fully stirred with 10 mL of absolute ethanol and 0.7 mL of H2O, and then 0.8 g of CH3COONa was added. The mixture was transferred to a reaction kettle and hydrothermally treated at 180 °C for 12 h. It was naturally cooled to room temperature, washed with deionized water, and the red precipitate was collected by centrifugation. Subsequently, it was dehydrated in a drying oven at 60 °C. The obtained red powder was prepared into a 0.1 mg / mL red suspension.

[0035] (3) 1 mL of the 0.1 mg / mL red suspension prepared in (2) was dropped into 2 g of the precursor complex prepared in (1), and then 1 mL of distilled water was additionally added to mix it evenly. Subsequently, it was transferred to a crucible and heated in a muffle furnace at 550 °C for 4 h. After cooling to room temperature, 400 mg of the product was taken out and heated in a muffle furnace at 550 °C for 1.5 h to obtain the product.

[0036] B. Photoreforming PET Hydrogen Production Process

[0037] 20 mg of the sample was dispersed in 50 mL of 1 M PET hydrolyzate, and platinum was loaded on the catalyst by in-situ photoreduction using 250 μL of H2PtCl6·6H2O aqueous solution. After that, vacuum was evacuated for 30 min to remove the residual gas contained in the system. The solution was continuously stirred under the light source of a 300 W xenon lamp equipped with a filter (λ>420 nm and AM 1.5G). The hydrogen production was analyzed by gas chromatograph, and high-purity nitrogen was used as the carrier gas during the entire reaction process. Data was recorded every 1 h, and 5 h was used as a cycle. Finally, the peak area shown in the gas chromatogram was converted into the actual hydrogen production in μmol g -1 h -1 .

[0038] Under visible light irradiation, the hydrogen production of UCN / PAN / α-Fe2O3-1 was 273.051 μmol g -1 h -1 .

[0039] Under AM 1.5G irradiation, the hydrogen production of UCN / PAN / α-Fe2O3-1 was 2473 μmol g -1 h -1 .

[0040] Example 2

[0041] A. Synthesis of Ultrathin Carbon Nitride / Polyacrylonitrile / Iron 2 Oxide (UCN / PAN / α-Fe2O3-2) Composites

[0042] (1) 20 mg of polyacrylonitrile and 2 g of melamine were mixed and ground, and then the mixture was transferred to a crucible and heated at 550° C. for 4 h in a muffle furnace. After cooling to room temperature, the mixture was washed with distilled water and anhydrous ethanol and centrifuged. The precipitate was collected and dried at 60° C. overnight.

[0043] (2) 0.273 g of FeCl3·6H2O was fully stirred with 10 mL of anhydrous ethanol and 0.7 mL of H2O, and then 0.8 g of CH3COONa was added. The mixture was transferred to a reactor and subjected to hydrothermal treatment at 180°C for 12 h. The mixture was naturally cooled to room temperature, washed with deionized water, and the red precipitate was collected by centrifugation and then dehydrated in a drying oven at 60°C. The resulting red powder was prepared into a 0.1 mg / mL red suspension.

[0044] (3) Drop 2 mL of the 0.1 mg / mL red suspension prepared in (2) into the 2 g precursor complex prepared in (1), then add an additional 1 mL of distilled water to mix it thoroughly, and then transfer it to a crucible and heat it in a muffle furnace at 550 °C for 4 h. After cooling to room temperature, take out 400 mg of the product and heat it in a muffle furnace at 550 °C for 1.5 h to obtain it.

[0045] B. Hydrogen production process of photo-reforming PET

[0046] Disperse 20 mg of the sample in 50 mL of 1 M PET hydrolysis solution, and use 250 μL of aqueous H2PtCl6·6H2O solution for in-situ photoreduction to load platinum on the catalyst. Then evacuate for 30 min to remove the residual gas contained in the system. Irradiate under a 300 W xenon lamp equipped with a filter (λ>420 nm and AM 1.5G), and continuously stir the solution. Analyze the hydrogen production with a gas chromatograph, using high-purity nitrogen as the carrier gas throughout the reaction process, record the data every 1 h, with 5 h as a cycle, and finally convert the peak area shown in the chromatogram of the gas chromatograph into the actual hydrogen production amount, with the unit of μmol g -1 h -1 。

[0047] Under visible light irradiation, the hydrogen production amount of UCN / PAN / α-Fe2O3-2 is 307.554 μmol g -1 h -1 。

[0048] Under AM 1.5G irradiation, the hydrogen production amount of UCN / PAN / α-Fe2O3-2 is 3796 μmol g -1 h -1 。

[0049] Example 3

[0050] A. Synthesis of ultrathin carbon nitride / polyacrylonitrile / iron oxide 3 (UCN / PAN / α-Fe2O3-3) composite

[0051] (1) Mix 20 mg of polyacrylonitrile and 2 g of melamine evenly and then grind them. Subsequently, transfer the mixture to a crucible and heat it in a muffle furnace at 550 °C for 4 h. After cooling to room temperature, wash and centrifuge with distilled water and absolute ethanol, collect the precipitate, and dry it overnight at 60 °C.

[0052] (2) 0.273 g of FeCl3·6H2O was thoroughly stirred with 10 mL of absolute ethanol and 0.7 mL of H2O, and then 0.8 g of CH3COONa was added. The mixture was transferred to a reaction kettle and hydrothermally treated at 180 °C for 12 h. It was naturally cooled to room temperature, washed with deionized water, and the red precipitate was collected by centrifugation and then dehydrated in a drying oven at 60 °C. The obtained red powder was prepared into a red suspension with a concentration of 0.1 mg / mL.

[0053] (3) 3 mL of the 0.1 mg / mL red suspension prepared in (2) was dropped into the 2 g of precursor complex prepared in (1), and then 1 mL of distilled water was additionally added to make it mix evenly. Subsequently, it was transferred to a crucible and heated in a muffle furnace at 550 °C for 4 h. After cooling to room temperature, 400 mg of the product was taken out and heated in the muffle furnace at 550 °C for 1.5 h to obtain the product.

[0054] B. Hydrogen production process of photocatalytic reforming of PET

[0055] 20 mg of the sample was dispersed in 50 mL of 1 M PET hydrolysis solution, and platinum was loaded onto the catalyst by in-situ photoreduction using an aqueous solution of 250 μL of H2PtCl6·6H2O. Then, vacuum pumping was carried out for 30 min to remove the residual gas contained in the system. Irradiation was carried out under a light source of a 300 W xenon lamp equipped with a filter (λ>420 nm and AM 1.5G), and the solution was continuously stirred. The hydrogen production was analyzed by a gas chromatograph, and high-purity nitrogen was used as the carrier gas throughout the reaction process. Data was recorded every 1 h, and 5 h was taken as a cycle. Finally, the peak area shown in the chromatogram of the gas chromatograph was converted into the actual hydrogen production, with the unit of μmol g -1 h -1 。

[0056] Under visible light irradiation, the hydrogen production of UCN / PAN / α-Fe2O3-3 was 557.081 μmol g -1 h -1 。

[0057] Under AM 1.5G irradiation, the hydrogen production of UCN / PAN / α-Fe2O3-3 was 4143 μmol g -1 h -1 。

[0058] Example 4

[0059] A. Synthesis of ultrathin carbon nitride / polyacrylonitrile / iron oxide 4 (UCN / PAN / α-Fe2O3-4) composite

[0060] (1) 20 mg of polyacrylonitrile and 2 g of melamine were mixed and ground, and then the mixture was transferred to a crucible and heated at 550° C. for 4 h in a muffle furnace. After cooling to room temperature, the mixture was washed with distilled water and anhydrous ethanol and centrifuged. The precipitate was collected and dried at 60° C. overnight.

[0061] (2) 0.273 g of FeCl3·6H2O was fully stirred with 10 mL of anhydrous ethanol and 0.7 mL of H2O, and then 0.8 g of CH3COONa was added. The mixture was transferred to a reactor and subjected to hydrothermal treatment at 180°C for 12 h. The mixture was naturally cooled to room temperature, washed with deionized water, and the red precipitate was collected by centrifugation and then dehydrated in a drying oven at 60°C. The resulting red powder was prepared into a 0.1 mg / mL red suspension.

[0062] (3) Add 4 mL of the 0.1 mg / mL red suspension prepared in (2) to 2 g of the precursor complex prepared in (1), and then add 1 mL of distilled water to mix thoroughly. Then transfer the mixture to a crucible and heat it in a muffle furnace at 550 °C for 4 h. After cooling to room temperature, take out 400 mg of the product and heat it in a muffle furnace at 550 °C for 1.5 h.

[0063] B. Photoreforming of PET to produce hydrogen

[0064] 20 mg of the sample was dispersed in 50 mL of 1 M PET hydrolyzate, and platinum was loaded on the catalyst by in-situ photoreduction using 250 μL of H2PtCl6·6H2O aqueous solution. After that, vacuum was evacuated for 30 min to remove the residual gas contained in the system. The solution was continuously stirred under the light source of a 300 W xenon lamp equipped with a filter (λ>420 nm and AM 1.5G). The hydrogen production was analyzed by gas chromatograph, and high-purity nitrogen was used as the carrier gas during the entire reaction process. Data was recorded every 1 h, and 5 h was used as a cycle. Finally, the peak area shown in the gas chromatogram was converted into the actual hydrogen production in μmol g -1 h -1 .

[0065] Under visible light irradiation, the hydrogen production of UCN / PAN / α-Fe2O3-4 was 182.339 μmol g -1 h -1 .

[0066] Under AM 1.5G irradiation, the hydrogen production of UCN / PAN / α-Fe2O3-4 was 2343 μmol g -1 h -1 .

[0067] Comparison Example

[0068] A. Synthesis of Bulk Graphitic Carbon Nitride (g-C3N4)

[0069] Weigh 2 g of melamine and transfer it to a crucible. Calcinate it in a muffle furnace at 550 °C for 4 h. Grind the obtained product thoroughly to get the desired product.

[0070] B. Photoreforming Process for Hydrogen Production from PET

[0071] Disperse 20 mg of the sample in 50 mL of 1 M PET hydrolysis solution. Use 250 μL of aqueous H2PtCl6·6H2O solution for in-situ photoreduction to load platinum onto the catalyst. Then conduct vacuum pumping for 30 min to remove the residual gas in the system. Irradiate under a 300 W xenon lamp equipped with a filter (λ>420 nm and AM 1.5G), and continuously stir the solution. Analyze the hydrogen production using a gas chromatograph. High-purity nitrogen is used as the carrier gas throughout the reaction process. Record data every 1 h, with 5 h as a cycle. Finally, convert the peak area shown in the chromatogram of the gas chromatograph into the actual hydrogen production amount, with the unit of μmol g -1 h -1 。

[0072] Under visible light irradiation, the hydrogen production amount of g-C3N4 is 141.755 μmol g -1 h -1 。

[0073] Under AM 1.5G irradiation, the hydrogen production amount of g-C3N4 is 688 μmol g -1 h -1 。

[0074] Electrochemical test conditions:

[0075] (1) The electrolyte used is 0.5 mol / L aqueous Na2SO4 solution;

[0076] (2) The working electrode is an ultrathin carbon nitride / polyacrylonitrile / iron oxide composite photoanode, the Ag / AgCl electrode is used as the reference electrode, and the Pt wire is used as the counter electrode;

[0077] (3) The light source for the electrochemical test is a 300 W xenon lamp, and the actual light power density irradiated on the electrode surface is 100 mW cm -2 ;

[0078] (4) The model of the electrochemical workstation used is CHI 760E from Shanghai Chenhua Co., Ltd.

[0079] Example 3 represents the optimal reaction conditions, with the highest hydrogen production from the photoreforming of PET. The morphology and microstructure of bulk graphitic carbon nitride (g-C3N4) and ultrathin graphitic carbon nitride / polyacrylonitrile / iron oxide composites were studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). As Figure 1 shown in (a) of Figure 1 , g-C3N4 exhibits a classic bulk stacked structure. Figure 1 Figures (c) and (d) of Figure 1 are the TEM images of UCN / PAN / α-Fe2O3. The lattice fringe spacing d = 0.251 nm in the selected area of (d) corresponds to the (110) plane of α-Fe2O3, indicating that α-Fe2O3 is successfully loaded on the catalyst.

[0080] As Figure 2 shown in the infrared spectrum of (a), the ultrathin graphitic carbon nitride / polyacrylonitrile / iron oxide composites and bulk graphitic carbon nitride prepared in different examples have obvious diffraction peaks at 3000 - 3600 cm -1 , 1210 - 1750 cm -1 and 806 cm -1 . The characteristic broad peak observed in the range of 3000 - 3600 cm -1 is attributed to the symmetric stretching vibration of -NH2 / -NH groups. The typical peaks in the range of 1210 - 1750 cm -1 correspond to the stretching mode of aromatic CN heterocycles, while the typical peak at 806 cm -1 is the out-of-plane bending vibration of the triazine ring. The crystal property transformation of g-C3N4 and UCN / PAN / α-Fe2O3 was determined by X-ray diffraction testing. As Figure 2 shown in (b), the XRD pattern of g-C3N4 shows two characteristic peaks at 13.1° and 27.1°, corresponding to the in-plane structural stacking (100) and interlayer stacking (002) of the aromatic chain segments of g-C3N4, respectively. The sample of Example 4 has a weak peak at 35.6°, corresponding to the (110) plane of α-Fe2O3. The weak signal of the (110) plane in other samples is due to the low addition amount of α-Fe2O3.

[0081] Figure 3 Figures (a - d) reproduce the high-resolution XPS spectra of g-C3N4 and UCN / PAN / α-Fe2O3-3. The XPS elemental scanning spectra of g-C3N4 and UCN / PAN / α-Fe2O3-3 correspond to the C1s peak in Figure 3 (b) and Figure 3The N 1s peak in (c). Four peaks appeared in the XPS C 1s spectrum of UCN / PAN / α-Fe2O3-3, with binding energies of 284.8 eV (C-C), 285.9 eV (C-O), 288.1 eV (C-N═C), and 293.9 eV (π-electron localization), respectively. Generally, in a similar bonding environment, atoms will exhibit similar binding energies. The binding energy of bulk carbon nitride (g-C3N4) is 288.2 eV. Similarly, the XPS N 1s spectrum of UCN / PAN / α-Fe2O3-3 also shows four peaks, with binding energies of 398.4 eV (C═N-C), 399.4 eV (N-H), 400.6 eV (N-(C)3), and 404.1 eV (π-electron localization), respectively. The binding energy of bulk carbon nitride (g-C3N4) in the XPS N 1s spectrum is 398.6 eV. The results show that compared with g-C3N4, the incorporation of PAN and α-Fe2O3 led to a low shift in binding energy by 0.1 eV and 0.2 eV, respectively. This indicates that there is a π-π interaction between PAN, α-Fe2O3, and g-C3N4, and the slight change in binding energy can be used as supplementary evidence for the addition of PAN and α-Fe2O3 to the carbon nitride ring, which is consistent with the XRD and TEM results. As Figure 3 shown in (d), the O 1s peak of g-C3N4 is attributed to surface-adsorbed CO2 and H2O. The XPS O 1s spectrum of UCN / PAN / α-Fe2O3-3 shows three binding energy peaks, namely 531.2 eV (Fe-O-C), 532.5 eV (C═O), and 533.8 eV (O-H). Figure 2 Figure (c) is the high-resolution Fe 2p XPS spectrum of UCN / PAN / α-Fe2O3-3. The presence of Fe was detected, and the binding energies were 711.2 eV and 725.2 eV, respectively, attributed to Fe 3+ , which further proves that α-Fe2O3 is loaded on the catalyst surface.

[0082] To further explore the changes in the photoelectrochemical properties of the ultrathin carbon nitride / polyacrylonitrile / iron oxide composite under light illumination, solid-state UV, Mott-Schottky tests, electrochemical impedance, and transient photocurrent tests were first performed on the g-C3N4 and UCN / PAN / α-Fe2O3 photocatalytic materials. Figure 2 Figure (d) uses ultraviolet-visible diffuse reflectance spectroscopy (DRS) to achieve the optical properties of g-C3N4 and UCN / PAN / α-Fe2O3. Compared with bulk carbon nitride (g-C3N4), UCN / PAN / α-Fe2O3 exhibits significantly enhanced light absorption ability. Figure 2(e-i) are the Tauc plots of g-C3N4 and UCN / PAN / α-Fe2O3. It can be clearly seen that the band gap of g-C3N4 is 2.68 eV, while that of UCN / PAN / α-Fe2O3-3 is reduced to 2.41 eV. The reduction of the band gap is more beneficial to improving the light absorption ability and the migration of electrons.

[0083] Figure 4 (a-e) are the Mott-Schottky plots of g-C3N4 and UCN / PAN / α-Fe2O3 materials. The slopes of the Mott-Schottky (M-S) curves of g-C3N4 and UCN / PAN / α-Fe2O3-3 are both positive, confirming the n-type nature of the semiconductors. The flat band potential (EFB) of g-C3N4 is -1.14 eV (vs. Ag / AgCl), and that of UCN / PAN / α-Fe2O3-3 is -0.76 eV. Generally, the CB potential of an n-type semiconductor is about 0.1 eV higher than the EFB potential. Therefore, the CB potentials of g-C3N4 and UCN / PAN / α-Fe2O3-3 are -1.04 eV and -0.66 eV, respectively, and the VB potentials are 1.64 eV and 1.75 eV, respectively. The above results indicate that adding a small amount of PAN and α-Fe2O3 to g-C3N4 broadens the π-conjugated system, enhances the light absorption ability, and reduces the band gap.

[0084] Figure 5 In (a) and (b), the transient photocurrent test shows that UCN / PAN / α-Fe2O3 has a better photocurrent response and a higher photocurrent density, indicating that more photogenerated charges are generated. The arc radius of the semicircular Nyquist curve of the electrochemical impedance spectroscopy (EIS) gradually decreases, indicating that more active sites are exposed on the catalyst surface and the energy barrier for charge transfer is reduced. The EIS of UCN / PAN / α-Fe2O3-3 is the lowest, indicating that the strong electron coupling bond (Fe-O-C) formed on the carbon nitride ring can greatly enhance charge transport. As Figure 5 As shown in (g), the sample UCN / PAN / α-Fe2O3-3 exhibits a significantly enhanced electron paramagnetic resonance (EPR) signal, indicating that there are more unpaired electrons in the material. The calculated g value is about 2.003, indicating the presence of oxygen vacancies. In addition, compared with g-C3N4, the photoluminescence (PL) signal peak of UCN / PAN / α-Fe2O3-3 is stronger ( Figure 5(d)). The stronger the PL fluorescence signal, the higher the content of oxygen vacancies and oxygen defects on the catalyst surface. In addition, during the photocatalytic reaction, oxygen vacancies and defects can serve as capture centers for photogenerated electrons, effectively inhibiting the recombination of photogenerated electron-hole pairs. Oxygen vacancies can promote the adsorption of oxygen, resulting in a strong interaction between the photoinduced electrons bound in the oxygen vacancies and the adsorbed oxygen. This result indicates that the combination of photoinduced electrons with oxygen vacancies can simultaneously generate oxygen free radicals by capturing photoinduced electrons from adsorbed oxygen. Therefore, oxygen vacancies and defects are beneficial to photocatalytic reactions because they have the ability to promote the oxidation of organic matter by oxygen free radicals. This shows that the stronger the photoluminescence (PL) intensity, the greater the number of oxygen vacancies and defects, and the better the photocatalytic performance. At the same time, the time-resolved photoluminescence (TR-PL) spectrum ( Figure 5 (c) shows that the average fluorescence lifetimes of g-C3N4 and UCN / PAN / α-Fe2O3-3 are 5.17ns and 7.24ns, respectively. It is worth noting that compared with g-C3N4, the fluorescence lifetime of UCN / PAN / α-Fe2O3-3 is prolonged, indicating a higher transfer efficiency of photogenerated carriers. The extension of the fluorescence lifetime means that the photogenerated carriers have more time to interact with the reactant molecules, thereby improving the catalytic efficiency. According to the Urbach formula, the band edge of the mid-gap state can be roughly shown in combination with the constant VB position, as Figure 5 (h) shows that the intermediate state of UCN / PAN / α-Fe2O3-3 is obviously biased towards the valence band top VBM. The transition barrier of holes from VB to the intermediate state is extremely low, and they are easily captured by the intermediate state and participate in the surface oxidation reaction. Electrons remain in the conduction band (CB) and participate in the reduction reaction. Therefore, the CB and VB energy levels can be connected to the E g Defined by a combination of values.

[0085] like Figure 6As shown in (a)-(d), in order to investigate the hydrogen production activity of ultrathin carbon nitride / polyacrylonitrile / iron oxide composites prepared by different examples under the conditions of λ>420 nm and AM 1.5G illumination, photocatalytic reforming PET hydrogen production tests were carried out on g-C3N4, UCN / PAN / α-Fe2O3-x (x = 1, 2, 3, 4). Due to the extremely high recombination rate of photo-generated carriers in g-C3N4, g-C3N4 exhibits poor hydrogen production activity under visible light and AM 1.5G illumination. The modified photocatalytic materials have significantly enhanced hydrogen production activity. Surprisingly, the photocatalytic reforming PET hydrogen generation rate of UCN / PAN / α-Fe2O3-3 is the highest, reaching 557.081 μmol / g / h and 4143 μmol / g / h under visible light and AM 1.5G illumination, respectively, which are approximately 3.93 times and 6.2 times the hydrogen production rates of g-C3N4 under the same conditions. The excellent photocatalytic activity of the best sample is attributed to the new chemical electron migration channels formed by the strong Fe-O-C electron coupling bonds, which enhance the migration rate of photo-generated carriers and expose more active sites.

[0086] The above are only the embodiments of the present invention, and do not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the specification of the present invention, or directly or indirectly applied in other related technical fields, shall be equally included in the patent protection scope of the present invention.

Claims

1. Preparation method of ultra-thin carbon nitride / polyacrylonitrile / iron oxide composite material, characterized in that: The following steps are involved: (1) mixing polyacrylonitrile and melamine uniformly and grinding them, then transferring the mixture into a crucible and heating the mixture in a muffle furnace at 540-560° C. for 4-6 hours, cooling the mixture to room temperature, washing the mixture with distilled water and anhydrous ethanol, centrifuging the mixture, collecting the precipitate, and drying the mixture to obtain a precursor composite; (2) FeCl3·6H2O, anhydrous ethanol and H2O are fully stirred, and then CH3COONa is added, and the mixture is transferred to a reactor, and hydrothermally treated at 170-190°C for 10-14 hours, and naturally cooled to room temperature, washed with deionized water, and the red precipitate is collected by centrifugation, dried and dehydrated, and the obtained red powder α-Fe2O3 is prepared into a red suspension of a certain concentration; (3) The red suspension obtained in step (2) is dripped into the precursor composite prepared in step (1), and then distilled water is added to mix it thoroughly, and then it is transferred to a crucible and calcined for the first time at 540-560° C. in a muffle furnace for 4-6 hours. After cooling to room temperature, it is calcined for the second time at 540-560° C. in a muffle furnace for 1-2 hours to obtain an ultra-thin carbon nitride / polyacrylonitrile / iron oxide composite material.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of polyacrylonitrile to melamine is 0.02g:2g.

3. The preparation method according to claim 1, characterized in that: In step (1), the heating reaction temperature is 550° C. and the time is 4 hours.

4. The preparation method according to claim 1, characterized in that: In step (2), the usage ratio of FeCl3·6H2O, anhydrous ethanol, water and CH3COONa is 0.273 g:10 mL:0.7 mL:0.8 g.

5. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the hydrothermal treatment is 180° C. and the time is 12 h.

6. The preparation method according to claim 1, wherein: In steps (1) and (2), the drying temperature is 60°C.

7. The preparation method according to claim 1, characterized in that: In step (3), the ratio of the red suspension to the precursor complex is 1-4 mL: 2 g; wherein the concentration of the red suspension is 0.1 mg / mL.

8. The preparation method according to claim 1, characterized in that: In step (3), the temperature of the first calcination is 550° C. and the time is 4 h; the temperature of the second calcination is 550° C. and the time is 1.5 h.

9. Ultra-thin carbon nitride / polyacrylonitrile / iron oxide composite material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the ultra-thin carbon nitride / polyacrylonitrile / iron oxide composite material according to claim 9 for photocatalytic reforming of PET to produce hydrogen.